Use of Mifepristone and Sublingual Misoprostol for Early Medical Abortion - Mau Lin; Yiu-Tai Li; Fu-Min Chen; Shu-Fang Wu; Ching-Wan Tsai; Tien-Hui Chen; Tsung-Cheng Kuo (Elsevier, 2006)
Objective: Existing drug-induced abortion techniques involve oral administration of 200 mg of mifepristone, followed by oral administration of 600 mg of misoprostol 48 hours later, but the effects are variable. As revealed by recent research, sublingual and oral administrations of misoprostol are equally efficacious in terms of rapid absorption, but the former lasts longer in serum. Hence, in the near future, sublingual administration of misoprostol may become the most effective way to induce abortion. Materials and Methods: Women with intrauterine pregnancy up to 49 gestational days received vaginal ultrasonography, followed by oral administration of mifepristone 200 mg and sublingual administration of misoprostol 600 mg 48 hours later. They returned for follow-up consultations 3 and 14 days after. The definition of a successfully induced complete medical abortion was that the abortion occurred without surgery or evacuating the uterus. Results: A total of 356 women underwent medical abortion; the complete abortion rate was 98.3% (350 women). Medical abortion was unsuccessful in five (1.7%) women, who eventually had to undergo dilation and curettage. Patients found the side effects to be bearable; the reported satisfaction rate was 89.9% (325 women). Conclusion: Medical abortion for early termination of pregnancy should be achieved by oral administration of mifepristone, followed by sublingual administration of misoprostol.